Correlates of Low Testosterone and Symptomatic Androgen Deficiency in a Population-Based Sample - Hall, Susan A. (The Endocrine Society, 2008)
Context: Risk factors for low testosterone and symptomatic androgen deficiency (AD) may be modifiable. Objective: Our objective was to examine demographic, anthropometric, and medical correlates of low testosterone and symptomatic AD. Design: Data were used from the Boston Area Community Health Survey, an epidemiological study conducted from 2002–2005. Setting: Data were obtained from a community-based random sample of racially and ethnically diverse men. Patients or other Participants: Data were available for 1822 men. Main Outcome Measures: Multivariate logistic regression was used to estimate odds ratios (OR) and 95% confidence intervals (CI) for associations of covariates with 1) low testosterone and 2) symptomatic AD. The operational definition of low testosterone was serum total testosterone less than 300 ng/dl and free testosterone less than 5 ng/dl; symptomatic AD was defined as the additional presence of symptoms: any of low libido, erectile dysfunction, or osteoporosis or two or more of sleep disturbance, depressed mood, lethargy, or diminished physical performance. Results: Factors associated with low testosterone included age (OR = 1.36; 95% CI= 1.11–1.66, per decade), low per-capita income ($6000 or less per household member vs. more than $30,000; OR = 2.86; 95% CI = 1.39–5.87), and waist circumference (per 10-cm increase; OR = 1.75; 95% CI = 1.45–2.12). Only age (OR = 1.36; 95% CI = 1.04–1.77), waist circumference (OR = 1.88; 95% CI = 1.44–2.47), and health status (OR = 0.21; 95% CI = 0.05–0.92, excellent vs. fair/poor) were associated with our construct of symptomatic AD. Of all variables, waist circumference was the most important contributor in both models. Conclusions: Waist circumference is a potentially modifiable risk factor for low testosterone and symptomatic AD. Manifestation of symptoms may be a consequence of generally poor health status.